2018
DOI: 10.1021/acs.analchem.7b04539
|View full text |Cite
|
Sign up to set email alerts
|

Combining Anisotropic Etching and PDMS Casting for Three-Dimensional Analysis of Laser Ablation Processes

Abstract: State-of-the-art laser ablation (LA) depth-profiling techniques (e.g. LA-ICP-MS, LIBS, and LIMS) allow for chemical composition analysis of solid materials with high spatial resolution at micro- and nanometer levels. Accurate determination of LA-volume is essential to correlate the recorded chemical information to the specific location inside the sample. In this contribution, we demonstrate two novel approaches towards a better quantitative analysis of LA craters with dimensions at micrometer level formed by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Many degraded spectra were recorded close to the surface (left side in Figure , upper panel). We attribute this effect to the initial crater formation process, occurring typically during the first 5000 to 10 000 laser shots . Afterwards, the mass peak intensities and mass resolution stabilise, and only a few files have to be discarded in a random occurrence pattern.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many degraded spectra were recorded close to the surface (left side in Figure , upper panel). We attribute this effect to the initial crater formation process, occurring typically during the first 5000 to 10 000 laser shots . Afterwards, the mass peak intensities and mass resolution stabilise, and only a few files have to be discarded in a random occurrence pattern.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, when Q‐switched lasers (eg, Nd:YAG laser operating in the ns pulse range) are used, the shot‐to‐shot fluctuations of the pulse are commonly in the range of a few percent, but values high as 40% were measured in our previous measurements . If working close to the ablation threshold, such fluctuations can indeed have a strong impact on the ion production rates …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, it is well known that uniform laser erosion of semiconductors requires harsher ablation conditions than metals. 69,70 Therefore, optimal laser conditions had to be initially determined to promote a nonselective removal of the irradiated material above the Si ablation threshold that would at least reach the bottom of single TSV structures (50 μm deep). Thus dedicated LIMS ablation investigations were performed on the TSVs to determine optimal laser irradiances and number of applied laser pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated an exponential decrease of the ablation rate for Si and Cu substrates using the same instrument setup. 27 This results in decreased recorded signal intensity and therefore in a lower signal-to-noise-ratio of the detected mass peaks. The lateral averaging of the material, in comparison, keeps the ablation plane at constant depth and therefore also the amount of ablated material.…”
Section: Improvement Of Measurement Performance For Bulk Chemical Anamentioning
confidence: 99%